Optimal Cutoffs for the Diagnosis of Sarcopenia in Older Chinese Adults - Ge, Sheng; Du, Qin; Feng, Xiaohui; Liu, Yan; Wang, Hui; Hai, Shan; Shi, Xiaodong; Sun, Wenguang; Ma, Aiqin; Lv, Tingting; Liu, Haili; Pinupa, Venkata Saibaba; et al. (Frontiers in Nutrition, 2022)
Backgrounds The optimal criteria for sarcopenia in older Chinese population have not been defined. Consequently, this study aims to determine the optimal cutoffs of grip strength, appendicular skeletal muscle index (ASMI) using BIA and gait speed, comprising the best definition of sarcopenia for older Chinese populations. Methods 2,821 (1,398 males and 1,423 females) community-dwelling older people (≥60 years) and 409 (205 males and 204 females) young healthy adults (25–34 years) were recruited from three big cities of China. Besides gait speed and grip strength, we examined ASMI by BIA and dual-energy X-ray absorptiometry (DXA), comprising the three components of sarcopenia. DXA classification for low ASMI, 20th percentile among older adults in the study sample, was found the best compared with the other existing classification, 1 SD and 2 SD below the mean for young population, and was used as gold standard to determine the optimal cutoffs of BIA using receiver operating characteristics curves (ROC). The cutoffs of hand grip strength and gait speed were determined following the same rule. Results Using gender-specific 20th percentiles of DXA (6.53 kg/m2 for males and 5.40 kg/m2 for females), the cutoffs 7.05 kg/m2 for males and 5.85 kg/m2 for females were determined as optimal cutoffs of BIA by achieving the largest sensitivity (0.81, 95% CI: 0.63–0.93 for males and 0.90, 95% CI: 0.73–0.98 for females) and specificity greater than 0.80 (0.80, 95% CI: 0.72–0.87 for males and 0.81, 95% CI: 0.72–0.87 for females) in the ROC analysis. The 28.5 kg and 1.05 m/s for males and 18.6 kg and 1.01 m/s for females were determined as the cutoffs for handgrip strength and gait speed, respectively. Based on the derived cutoffs, 14.2% males and 15.7% females in the older Chinese study population were classified as sarcopenia. Conclusion 7.05 kg/m2, 28.5 kg and 1.05 m/s for males and 5.85 kg/m2, 18.6 kg and 1.01 m/s for females were selected as the optimal cutoffs for low ASMI by BIA, handgrip strength and gait speed, respectively. These optimal cut-offs will enhance practicability for screening sarcopenia in primary care and clinical settings.